2019
DOI: 10.1002/cctc.201900346
|View full text |Cite
|
Sign up to set email alerts
|

Models Facilitating the Design of a New Metal‐Organic Framework Catalyst for the Selective Decomposition of Formic Acid into Hydrogen and Carbon Dioxide

Abstract: Here we describe a new conceptual approach for the design of a heterogeneous metal‐organic framework (MOF) catalyst based on UiO‐67 for the selective decarboxylation of formic acid, a reaction with important applications in hydrogen storage and in situ generation of H2. Models for the {CuH} reactive catalytic site at the organic linker are assessed. In the first model system, gas‐phase mass spectrometry experiments and DFT calculations on a fixed charge bathophen ligated copper hydride complex, [(phen*)Cu(H)]2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Well-defined gasphase experiments can provide valuable insight into reaction mechanisms on a molecular level, [30][31][32] while spectroscopy based experiments can yield detailed insight into the molecular and electronic structure. 33,34 In the gas phase, many molecular mechanisms involving the activation of methane, 35,36 carbon dioxide [37][38][39][40] and elementary steps of hydrogen storage applications [41][42][43] have successfully been studied. Ultraviolet/visible/near-infrared (UV/vis/NIR) photodissociation spectroscopy is a very powerful tool to characterize the complex electronic structure of transition metal complexes and clusters in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Well-defined gasphase experiments can provide valuable insight into reaction mechanisms on a molecular level, [30][31][32] while spectroscopy based experiments can yield detailed insight into the molecular and electronic structure. 33,34 In the gas phase, many molecular mechanisms involving the activation of methane, 35,36 carbon dioxide [37][38][39][40] and elementary steps of hydrogen storage applications [41][42][43] have successfully been studied. Ultraviolet/visible/near-infrared (UV/vis/NIR) photodissociation spectroscopy is a very powerful tool to characterize the complex electronic structure of transition metal complexes and clusters in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental challenges of developing these zeolite-based "ship in a bottle" catalysts (Ozin&Gil, 1989), focused our attention on metal organic frameworks (MOFs) (Hoskins&Robson 1989;Hoskins&Robson 1990), which offer three types of potential catalytic sites, as illustrated for the UiO-67 MOF (Scheme 25c) (Huang et al, 2017). Of these, the organic linker, which can be functionalized to introduce a catalytic site, provides an attractive target for our gas-phase model studies (O'Hair et al, 2019).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…The experimental challenges of developing these zeolitebased "ship in a bottle" catalysts (Ozin & Gil, 1989), focused our attention on metal-organic frameworks (MOFs) (Hoskins & Robson 1989, which offer three types of potential catalytic sites, as illustrated for the UiO-67 MOF (Scheme 25c) (Huang et al, 2017). Of these, the organic linker, which can be functionalized to introduce a catalytic site, provides an attractive target for our gas-phase model studies (O'Hair et al, 2019). Experiments on the fixed-charge model 36d revealed that the same two-step catalytic cycle (Scheme 25a) operates, while DFT calculations showed that the mechanisms and energetics associated with the two-step catalytic cycle of simple gas-phase catalysts 36d-36f (Scheme 25d) are very similar to those of the models 36g and 36h of UiO-67 MOF (Scheme 25e).…”
Section: A Towards An Integrated Mechanistic Approach In Catalysismentioning
confidence: 99%
“…The general utility and versatility of gasphase studies has been established in many realms, such as organometallic chemistry and C-H bond activation. [60][61][62][63][64][65][66][67] Examples of gas-phase contributions to uranium chemistry include oxo-exchange of uranyl with water, [68] a nitrosyl complex, [69] a peroxide dimer, [70] and an "extreme" CCI. [71] Stand-alone com-putational studies have assessed stabilities of elementary CCIs in gas-phase uranyl dimers.…”
Section: +mentioning
confidence: 99%